2015
DOI: 10.1371/journal.pone.0142851
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Centimeter-Scale Spatial Variability of PAHs and Microbial Populations in the Rhizosphere of Two Plants

Abstract: Rhizoremediation uses root development and exudation to favor microbial activity. Thus it can enhance polycyclic aromatic hydrocarbon (PAH) biodegradation in contaminated soils. Spatial heterogeneity of rhizosphere processes, mainly linked to the root development stage and to the plant species, could explain the contrasted rhizoremediation efficiency levels reported in the literature. Aim of the present study was to test if spatial variability in the whole plant rhizosphere, explored at the centimetre-scale, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 70 publications
(82 reference statements)
1
31
1
Order By: Relevance
“…However, this does not mean the enrichment of GP degraders by PAH pollution, since they could be affected by soil characteristics or the presence of plant. It has been previously observed that abundance of PAH-RHDα gene was often changed by root exudates23, organic matter24 and pH25. Controlled experiments with more comprehensive and sensitive tests, for example the transcription activities analysis2627 are therefore required to reveal the effects of PAH pollution on degrader community.…”
Section: Resultsmentioning
confidence: 99%
“…However, this does not mean the enrichment of GP degraders by PAH pollution, since they could be affected by soil characteristics or the presence of plant. It has been previously observed that abundance of PAH-RHDα gene was often changed by root exudates23, organic matter24 and pH25. Controlled experiments with more comprehensive and sensitive tests, for example the transcription activities analysis2627 are therefore required to reveal the effects of PAH pollution on degrader community.…”
Section: Resultsmentioning
confidence: 99%
“…Anthropic soils can contain PAH concentrations beyond 1,000 mg.kg -1 (Biache et al, 2008;Ouvrard et al, 2013). But PAH concentrations can largely vary in soils from coking plant sites owing to contamination heterogeneity, age, natural attenuation with time, and to remediation measures (Bourceret et al, 2015).…”
Section: Pollutant Concentrationsmentioning
confidence: 99%
“…The present study focuses on the bacterial community structure along two plant root systems (alfalfa and ryegrass) in a PAH-contaminated soil in order to point out the principal environmental biotic and abiotic drivers at centimeter scale using rhizobox experimental device. Spatial variability of bacterial community has been rarely studied in the past, at small scale, and never in contaminated soil presenting spatial patchy distribution of pollutants and depth rhizosphere gradients as found in Bourceret et al (2015). Based on these previous findings, we hypothesized that bacterial community could be influenced by two main forcing factors identified previously: i) rhizosphere processes linked to plant species and root depth gradients of root biomass and carbon from exudates, and/or ii) pollutant content that shows a random spatial distribution with cold and hot spots of PAHs.…”
Section: R a F T 2015)mentioning
confidence: 99%
“…Europe) and ryegrass (Rye; Lolium multiflorum var. Podium) at 22.3 ± 2.0 seeds per cm 2 , plants were grown in a regulated growth chamber (22°C /18°C day/night, 80% relative humidity, ca 250 µmol photons m -2 s -1 , 16-hour photoperiod) (Bourceret et al 2015). Rhizoboxes were opened after 37 days (T37) when few roots reached the bottom of the rhizoboxes and root density gradients could easily be visualized for both plants.…”
Section: Experimental Device Sampling and Soil Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation